1997
DOI: 10.1159/000185470
|View full text |Cite
|
Sign up to set email alerts
|

Nerve Growth Factor Suppresses the Tumoral Phenotype of Human Prolactinomas

Abstract: We summarize here our data showing that various phenotypical characteristics distinguish prolactinoma cell lines obtained from responder and nonresponder patients, as defined by their responses to bromocriptine administration. Nonresponder cell lines have a higher degree of malignancy than responder cells and do not express D2 receptors for dopamine. Both cell lines express NGF receptors. Exposure of the most malignant nonresponder cell lines to NGF, both in vitro and when transplanted in vivo in nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…There are two general classes of prolactinomas, those which respond to treatment with a dopamine agonist with a cessation of lactotropic proliferation and those that do not. The nonresponsive tumors lack D2 receptors on the lactotropes and express low levels of NGF (116). Recently, it has been demonstrated that lactotropes from a non-responsive tumor, became responsive to dopamine agonist therapy after treatment with NGF, which caused the expression of the D2 receptors (117).…”
Section: Role Of Nerve Growth Factormentioning
confidence: 99%
“…There are two general classes of prolactinomas, those which respond to treatment with a dopamine agonist with a cessation of lactotropic proliferation and those that do not. The nonresponsive tumors lack D2 receptors on the lactotropes and express low levels of NGF (116). Recently, it has been demonstrated that lactotropes from a non-responsive tumor, became responsive to dopamine agonist therapy after treatment with NGF, which caused the expression of the D2 receptors (117).…”
Section: Role Of Nerve Growth Factormentioning
confidence: 99%